Caring for non-sedated mechanically ventilated patients in ICU: A qualitative study comparing perspectives of expert and competent nurses. (June 2019) - Mortensen, Camilla Bekker; Kjær, Maj-Brit Nørregaard; Egerod, Ingrid
Abstract: Background: Sedation practice has evolved from deep to lighter or no sedation in mechanically ventilated patients in the intensive care unit (ICU). The care of conscious intubated patients constitutes a change in the nurse-patient interaction. Objective: We aimed to compare the perspectives of expert and competent nurses regarding their interaction with non-sedated mechanically ventilated ICU patients. Method: The study had a qualitative comparative design applying semi-structured dyadic interviews. We interviewed five pairs of expert and competent ICU nurses with respectively >8 and 2–3 years of ICU experience and performed qualitative content analysis to explore the two perspectives. Findings: We identified four main categories illustrating complexities of nurse-patient interaction: Managing frustration, Attempting dialogue, Negotiating reality and Alleviating discomfort. Expert nurses expressed more frustration and ambivalence towards light sedation than competent nurses, who took awake patients for granted. All nurses experienced communication issues, demanding patients, and inability to provide adequate patient comfort. Conclusion: Our study added to the knowledge of nurse-patient interaction by describing issues of frustration, ambivalence and insecurity in a contemporary context of minimal sedation. Expert nurses were mere concerned by awake patients than competent nurses. Lighter sedation in ICU requires better staffing and improved communication tools.